Development of an aluminium coreless ironless generator for EV applications - Razali, Akhtar Razul
The presence of cog in ironcore generator is seen somehow restricting the application of the generator where low rotational torque is required. Cogging creates an attraction force between magnets and ironcore lamination in a generator. More power is required to overcome cogging before the generator can be spun continuously. With the increase of power output, the problem of cogging is also increased. Therefore, more power is required to overcome the increased torque. The research sought to fundamentally study the possibility of removing ironcore lamination in an electric generator. The generator was designed, fabricated and experimentally validated to qualify its no-load and loaded characteristics. The research began with fundamental studies on electric generator and eventually followed by the design concept. The concept was later analyzed in simulation mode by using FE software to study its characteristics in order to determine its optimum arrangements. Based on the optimum design obtained in the FE simulations, the generator was then developed and tested in experimental mode to qualify and quantify its qualitative and quantitative characteristics. Since the generator was made coreless and ironless, the cogging torque was therefore fully eliminated. Results in both simulation and experimental modes showed good agreement between the two. The generator managed to generate a few hundred watts of power and the efficiency was rated to be approximately 75%. Based on the quantitative experiments, pure sinusoidal 3-phase voltage wave was captured on a scope. The voltage increased with the increase of rotational speed. Cog-free motion was found to have demonstrated low starting torque spin. Hence, it can be concluded that it would be suitable for use in low torque application. Many applications can benefit from this generator such as in electric generation itself, wind turbine as well as applications in the automotive industry.